Synthesis, Characterization and Antitumor Activity of Some New Oganotellurium Compounds Containing Azomethine Group, Part One (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
New tellurated schiff bases were synthesized by the reaction of the corresponding mercurated Schiff  bases compounds A1-A3 with tellurium tetrabromide in 1:1 mole ratio and  that  gave organyltellurium tribromides  A4-A6.  On the other hand, when mercurated schiff bases and tellurium tetrabromide brought  together in 2:1 mole ratio gave diorganyltellurium dibromides compounds A10-A12 followed by reduction with hydrazine hydrate gave new diorganyl tellurides A13-A15.  Reduction of compounds A4-A6 by  hydrazine hydrate gave new ditellurides A7-A9.  All compounds were characterized by elemental analysis, IR, 1H , 13C NMR, HSQC-NMR and mass spectra.  Invitro anti-tumor bioactivity of some compounds were tested.